The Pharmacokinetics of Once-Daily Dosing With Gentamicin in Women With Postpartum Endometritis - J. A. Sunyecz; H. C. Wiesenfeld; R. P. Heine (Hindawi Limited, 1998)
Conclusions: Once-daily dosing with gentamicin in women with postpartum endometritis achieves therapeutic peak levels without drug accumulation. Substantial cost savings are realized with this dosing regimen.